Increasing age at presentation for patients with ankylosing spondylitis. Issue 3 (March 1992) - Will, R; Calin, A; Kirwan, J
Abstract : An analysis of the age at first presentation was undertaken in patients with ankylosing spondylitis and mechanical back pain seen at the London Hospital department of rheumatology between 1952 and 1983. There was a significant positive correlation with the calendar year of presentation in the patients with ankylosing spondylitis but a negative correlation in those with mechanical back pain. An increasing age at presentation in ankylosing spondylitis is likely to be due to an increasing age at disease onset--all anticipated biases would act in the opposite direction. This observation in a prospective study supports the findings of other studies using different epidemiological techniques.